Estimation of genetic diversity for quantitative traits of commercial wheat (Triticum aestivum) - Rasheed, Adnan; Solangi, Abdul Malik (Journal of Scientific Agriculture, 2017)
This research was conducted to assess the performance of wheat genotypes and to detect genotypes with adult plant resistance by evaluating them in a trap nursery. 36 commercial wheat cultivar were used in experiment. Morocco was sown on four sides of trial. Material was sown in augmented design. The data was recorded on different quantitative like Plant height (cm), no. of tillers/plant, spike length (cm), no of spikelets/plant, peduncle length (cm), stem diameter (mm) and flag leaf area. Selection of genotypes could be done from two main clusters to make cross for improvement of traits. No of tillers/plant, peduncle length, spike/length, spikelets/plant and plant height showed large genetic variability in Biplot and these variables could be used as selection criteria. Pak-81, Sindh-81, Mexipak-65, Sarsabaz, Chakwal-86 and Kiran-95 so these cultivars could be potentially used in future breeding programme for improvement of several quantitative traits according to results of Biplot analysis. Following genotypes were found moderate resistant against yellow rust viz. Anmol-9, Bahawalpur-200 and Bakhtawar-92 and could be used further in future breeding programme to stand against yellow ruts pressure. Maxipak-65 and WL-711 need to improve by incorporating yellow rust resistant genes.